Preston lee's beginner english lesson 1 ebook 60 for arabic speakers. - Lee, Preston (Smashwords Edition, 2020)
Everything a beginner needs for learning English in one book! This book contains lessons 1 - 60 from the best-selling book, Preston Lee's Beginner English 100 Lessons. Have fun and learn English the easy way. This book has been written for all ages, children and adults alike. - 60 excellent lessons for everyday English - 120 fun worksheets for easy learning - Over 120 useful sentence patterns - Practice tests to reinforce learning - Step-by-step grammar development - Frequently used verbs in 4 grammatical forms - 60 practical and commonly used idioms - Vocabulary words include Arabic translation Preston Lee's Beginner English is the absolute best way to learn English. Written by ESL specialists, Kevin Lee and Matthew Preston have taught English as a Second Language for over 20 years around the world. The lessons in this book have been carefully chosen to help the learner really understand a range of topics for everyday talk. This book includes everything you need to become an excellent and fluent English speaker!